Application of spectral method for vibration-induced high-cycle fatigue evaluation of an HP turbine blade - Ubulom, Iroizan (American Society of Mechanical Engineers (ASME), 2020)
A fluid-structure interaction coupling is implemented for a forced-response, vibration-induced fatigue life estimation of a high-pressure turbine blade. Two simulations approaches; fully-coupled and uncoupled methods, are implemented to investigate the influence of fluid-solid coupling on a turbine blade structural response. The fatigue analysis is performed using the spectral moments estimated from the response power spectral densities of the two cases. The method is compared against similar prediction using the time-domain approach with mean stress correction. Correspondingly, the mean stress and multiaxiality effects are also accounted for in the frequency domain spectral approach. In the mean stress case, a multiplication coefficient is derived based on the Morrow equation, while the case of multiaxiality is based on a criterion which reduces the triaxial stress state to an equivalent uniaxial stress using the critical plane assumption. The analyses show that while the vibration-induced stress histories of both simulation approaches are stationary, they violate the assumption of normality of the frequency domain approaches. The stress history profiles of both processes can be described as platykurtic with the distributions having less mass near its mean and in the tail region, as compared to a Gaussian distribution with an equal standard deviation. The fully-coupled method is right leaning with positive skewness while the uncoupled approach is left leaning with negative skewness. Noticeable differences were found in the peak distribution of the normal stresses for both methods, but the predicted Euler angle orientations were consistent in both cases.
Keywords: turbine blade; high-cycle fatigue; Dirlik damage method; spectral moments; probability density functions